Konsep Hijab Menurut Murtadha Muthahhari dan Relevansinya dengan Persoalan Etis dan Teologis - Annisa Tawakalni; Radea Yuli Ahmad Hambali; Ahmad Gibson Albustomi (Jurnal Riset Agama, 2022)
Hijab in Islam is an order to women to cover his body when socializing with the opposite sex. Hijab can be a "boundarous" of the intervals between women and men to correspond to ethical values so as not to lead to adultery. However, the current reality shows the free social and women-related social reachers have reached at a worrying rate, especially targeting millenniums that can freely associate with the opposite sex. This study discusses the concept of Hijab according to Murtadha Muthahhari and its relevance to the ethical and theological issues. The purpose of this study is to describe the concept of Hijab according to Murtadha Muthahhari and its relevance with the ethical and theological issues. This research applies qualitative methods to literature approaches. The results of this study indicate that in human history, the fundamental reasons of the empowerment of the hijab for women. Among the reasons of philosophical, economic, social, ethical and psychological. For Muthahhari the reasons do not match the teachings of Islam. Islam has its own reasons for the empowerment of hijab to the Muslims. Among them are families, the welfare of women, and society.